2021
DOI: 10.1073/pnas.2100786118
|View full text |Cite
|
Sign up to set email alerts
|

Comparing information diffusion mechanisms by matching on cascade size

Abstract: Do some types of information spread faster, broader, or further than others? To understand how information diffusions differ, scholars compare structural properties of the paths taken by content as it spreads through a network, studying so-called cascades. Commonly studied cascade properties include the reach, depth, breadth, and speed of propagation. Drawing conclusions from statistical differences in these properties can be challenging, as many properties are dependent. In this work, we demonstrate the essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 34 publications
2
42
0
Order By: Relevance
“…Although fake news can thus spread faster and deeper than true news, it is important to emphasize that these findings are based on a relatively narrow definition of fact-checked news (see Box 2 and ref. 70 ), and more recent research has pointed out that these estimates are likely platform-dependent 72 . Importantly, several studies have now shown that fake news typically represents a small part of people's overall media diet and that the spread of misinformation on social media is highly skewed so that a small number of accounts are responsible for the majority of the content that is shared and consumed, also known as 'supersharers' and 'superconsumers' 3,24,73 .…”
Section: Spreadmentioning
confidence: 99%
See 1 more Smart Citation
“…Although fake news can thus spread faster and deeper than true news, it is important to emphasize that these findings are based on a relatively narrow definition of fact-checked news (see Box 2 and ref. 70 ), and more recent research has pointed out that these estimates are likely platform-dependent 72 . Importantly, several studies have now shown that fake news typically represents a small part of people's overall media diet and that the spread of misinformation on social media is highly skewed so that a small number of accounts are responsible for the majority of the content that is shared and consumed, also known as 'supersharers' and 'superconsumers' 3,24,73 .…”
Section: Spreadmentioning
confidence: 99%
“…Measuring the infodemic. To return to the viral analogy, researchers have adopted models from epidemiology, such as the susceptible-Infected-recovered (SIR) model, to measure and quantify the spread of misinformation in online social networks 17,70 . In this context, R 0 often represents individuals who will start posting fake news following contact with someone who is already 'infected' .…”
Section: Spreadmentioning
confidence: 99%
“…In addition, Friggeri et al (2014) find that corrections appearing online related to a specific unsubstantiated rumor can lead to a significant reduction in circulation. Juul and Ugander (2021) find that spreading behavior is similar for false and true news once the size of an information cascade is controlled for; the authors do find, however, that false‐news cascades are often larger. Thus, the evidence coming from the study of Internet data concerning the potential impact and magnitude of the misinformation problem for citizens is not more conclusive than the experimental evidence reviewed in the preceding sections.…”
Section: State Of the Artmentioning
confidence: 99%
“…Information transmission in the context of Information and Communication Technologies is a great opportunity to create a better-informed society, but in practice these technologies are also promoting phenomena such as viral spreading of fake news [1][2][3] , echo chambers [4][5][6] , perception biases such as false consensus or majority illusions 7 , as well as social polarization 5,6,8 . We understand by echo chambers situations in which the transmission of information among individuals belonging to the same opinion group is dominant, while transmission among individuals with different opinions is hindered.…”
Section: Introductionmentioning
confidence: 99%